PSYCHOLOGICAL WELL BEING UNTUK GURU MENGANTISIPASI KASUS BULLYING DI SEKOLAH - Hartati, Seri; Arisandi, Diki (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Bullying in the school environment is a serious issue that can negatively impact the psychological well-being of both students and teachers. Teachers play a crucial role in preventing and addressing bullying cases; however, they often face psychological pressure that may affect their effectiveness in handling such situations. This community service program aims to enhance teachers' psychological well-being by conducting an online survey to assess their preparedness in anticipating and managing bullying cases in schools. This initiative includes administering an online survey to evaluate teachers’ emotional regulation skills, stress management, resilience, and intervention strategies for handling bullying incidents. The methods employed consist of educational sessions and online surveys involving teachers in Pekanbaru. The results of this program indicate that psychological well-being plays a vital role in addressing bullying in schools. Therefore, psychological well-being-based education for teachers serves as a strategic step in the prevention and management of bullying in schools